Podpora ranljivim družinam in preventivno skupnostno delo kot posebna vidika antideložacijskega dela - Razpotnik, Špela (Socialno delo, 2018)
In addition to working with individual tenants in crisis situations within anti-eviction programme carried out by the Association Kings of the Street, additional two forms of work are being carried out: support for vulnerable families and preventive community work. These represent a more permanent and more prevention-oriented forms of support which is not carried out only in times of crisis, and not only focused on tenants and families in immediate crisis. In the framework of supporting families, the important role of voluntary workers should be emphasised, as well as the focus on sources of strength of families and the search for the optimum balance between structure and flexibility of support. Preventive community work pursues three main objectives: (1) creating a better climate and relations among the residents of a building or neighbourhood; (2) creating a culture of negotiation and taking care of their apartment and common areas; and (3) creating a relationship of trust between the staff of anti-eviction program and tenants. This should make work with tenants in times of threats of eviction easier and more efficient.
Keywords: housing; stanovanje; izključenost; exclusion; prostovoljno delo; voluntary work; ustvarjanje skupnosti; community building; Kings of the Street; Kralji ulice; advocacy; zagovorništvo